POTENSI BIOMASSA MANTANGAN (Merremia Peltata) DI TAMAN NASIONAL BUKIT BARISAN SELATAN - Santori Santori; Duryat Duryat; Trio Santoso (Forestry Study Program University Of Mataram, 2023)
Mantangan has properties that are detrimental to the environment, especially related to its invasive nature for conservation areas such as TNBBS. Mantangan plants can reduce the level of habitat quality and inhibit the mobility of large fauna in TNBBS. The condition of the fast growth rate of mantangan and some detrimental properties to the growth of other plants, this mantangan plant has the potential as a producer of biomass. The purpose of this study was to determine the potential of mature biomass per hectare at Pemerihan Resort TNBBS. Sampling with stratified sampling based on the canopy cover class strata found in Pemerihan Resort, namely meeting, medium, and rare. The results showed that the biomass in the three classes of dense canopy cover was different, namely dense canopy 179 kg/ha, medium 188 kg/ha, and rarely 192 kg/ha. These results showed that the three classes of canopy cover overgrown with invasive species were not significantly different. This means that the biomass content in the three canopy cover classes is not much different, because the area exposed to this invasive species is also filled with other vegetation. Tackling the impact of mantangan plants which are declared invasive in the resort area, it can be used as organic fertilizer because of the high biomass content of mantangan and fast growth as well as wild and invasive growth in TNBBS.